The Relationship of Self-Efficacy with the Career Readiness of Final Years Students in Islamic Religious Colleges - Khayatun Nufus Akhsania (P3M STAI Kuningan, 2026)
Background : Career readiness is an important aspect that final-year students must possess to successfully transition from higher education to the workforce. Students of Islamic Religious Higher Education Institutions (PTKI) are expected not only to have academic and religious competencies but also adequate career readiness to compete in an increasingly competitive job market. One psychological factor believed to influence career readiness is self-efficacy. Objectives : To determine the relationship between self-efficacy and career readiness among final-year students at Islamic Religious Higher Education Institutions (PTKI). Method : This study employed a quantitative approach with a correlational research design. The population consisted of final-year PTKI students, with a sample of 150 students selected through purposive sampling. Data were collected using the Self-Efficacy Scale and Career Readiness Scale, both of which had been tested for validity and reliability. Data analysis was conducted using Pearson’s Product Moment correlation. Finding and Implication : The results revealed a positive and significant relationship between self-efficacy and career readiness among final-year students (r = 0.682; p < 0.05). Students with higher levels of self-efficacy tended to demonstrate higher career readiness. These findings imply that confidence in one's abilities plays a crucial role in preparing students to enter the workforce. Therefore, career guidance and counseling services at PTKI should focus on strengthening students’ self-efficacy to enhance their career readiness. Conclusion : There is a significant positive relationship between self-efficacy and career readiness among final-year PTKI students. Enhancing self-efficacy can contribute to improving students’ preparedness for the world of work.